The changing geopolitics of Eastern Europe / edited by Andrew H. Dawson and Rick Fawn. - Dawson, Andrew H.; Fawn, Rick. (Frank Cass, 2002)
"This book explores the current uncertain geopolitical situation of the countries of central and eastern Europe, including some of those which are hoping to enter the European Union in the near future, some for which entry is far off, and some which may never seek or be eligible for membership. Particular attention is paid to Russia, Poland, Romania, Albania and the Visegrad initiative, and the current and future borders of Europe are considered in terms of culture, economy and political and security co-operation."--Jacket.